Expansion of Ethical, Legal and Social Implications in Science and Technology Policy: From genome editing and ai to economic security - HISHIYAMA, Yutaka (The Journal of Science Policy and Research Management, 2022)
With the great development of science and technology, Ethical, Legal and Social Implications, which addresses the social aspects of S&T, has been becoming more important and expanding in S&T policy. The concept of "comprehensive knowledge" was introduced in the 6th Science and Technology Innovation Basic Plan. ELSI has an affinity with it because ELSI is a main research subject of humanities and social sciences. In this paper, the author describes the current issues regarding ELSI in life sciences and discusses the trends of ELSI in the AI and IT. Also, he explains that the economic security is the range of ELSI. In addition, taking COVID-19, he points out that scientific advice from experts may not have been given properly to the Government and that Scientific advice is also within the scope of ELSI. He discusses who should give scientific advice and what kind of organization should be in charge.